Students’ Perception of Online Learning-based Padlet during Pandemic - Arimuliani Ahmad; Yassa Aura Rubayyi; Fauzul Etfita (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to investigate the perceptions of online learning occurring during the COVID-19 pandemic. This study was applied as a case study design. The population of the research was all the second-semester students of English Language Education at one of the private universities in Riau, Indonesia. The population in this study was 173 students, while the sample was selected using random cluster sampling, amounting to 79 students. Data were collected by a questionnaire consisting of 18 questions from five components of online learning using a 5 Likert Scale. The data presented that the dominant percentage of total students gave a positive preference for the utilization of Padlet as online learning media.